1996
DOI: 10.1021/ac960128s
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Method for Trifluoroacetic Acid in Water and Air Samples Using Headspace Gas Chromatographic Determination of the Methyl Ester

Abstract: An analytical method has been developed for the determination of trace levels of trifluoroacetic acid (TFA), an atmospheric breakdown product of several of the hydrofluorocarbon (HFC) and hydrochlorofluorocarbon (HCFC) replacements for the chlorofluorocarbon (CFC) refrigerants, in water and air. TFA is derivatized to the volatile methyl trifluoroacetate (MTFA) and determined by automated headspace gas chromatography (HSGC) with electron-capture detection or manual HSGC using GC/MS in the selected ion monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 77 publications
2
52
1
Order By: Relevance
“…TFA has become a ubiquitous contaminant and has been detected in a variety of environmental media, such as air (Frank et al, 1996), precipitation (Jordan and Frank, 1999;Scott et al, 2006;Zehavi and Seiber, 1996), fog (Römpp et al, 2001), surface waters (Cahill and Seiber, 2000;Scott et al, 2000Scott et al, , 2002Zhang et al, 2005), soils and pine needles Scott et al, 2005b), oceans (Frank et al, 2002;Scott et al, 2005a) and even in the snow of the Arctic and Antarctica (Von Sydow et al, 2000). TFA is extremely stable in the ambient and highly resistant to chemical and biological degradation under normal environmental condition (Emptage et al, 1997;Boutonnet et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TFA has become a ubiquitous contaminant and has been detected in a variety of environmental media, such as air (Frank et al, 1996), precipitation (Jordan and Frank, 1999;Scott et al, 2006;Zehavi and Seiber, 1996), fog (Römpp et al, 2001), surface waters (Cahill and Seiber, 2000;Scott et al, 2000Scott et al, , 2002Zhang et al, 2005), soils and pine needles Scott et al, 2005b), oceans (Frank et al, 2002;Scott et al, 2005a) and even in the snow of the Arctic and Antarctica (Von Sydow et al, 2000). TFA is extremely stable in the ambient and highly resistant to chemical and biological degradation under normal environmental condition (Emptage et al, 1997;Boutonnet et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although the observed TFA levels in aqueous environment were all below the safety level of 0.10 mg L −1 (Berends et al, 1999), high levels have been reported as early as in 1990s. For instance, TFA concentrations were reported as high as 40,900 ng L −1 in Pyramid Lake of the United States (Zehavi and Seiber, 1996); and the levels beyond 1000 ng L −1 were also recorded in rainwater around the world (Frank et al, 1995;Wujcik et al, 1998;Von Sydow et al, 2000;Berg et al, 2000;Scott et al, 2006). Due to the continual input to the environment and the accumulation in terminal water bodies, TFA levels in aqueous environment would keep increasing in the coming decades and more attention should be paid on its potential adverse effects (Berends et al, 1999;Boutonnet et al, 1999;Wiegand et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…80 Concentrations up to 350 ng L -1 in flowing surface waters have been reported from several locations. [81][82][83] However, in landlocked lakes, they may be as large as 40 000 ng L -1 . 81 Reports of TFA concentrations in oceans are generally less than or equal to 200 ng L -180, 81, 83 and much of this appears to have pre-industrial natural origins.…”
Section: Fluorinated Substancesmentioning
confidence: 99%
“…[81][82][83] However, in landlocked lakes, they may be as large as 40 000 ng L -1 . 81 Reports of TFA concentrations in oceans are generally less than or equal to 200 ng L -180, 81, 83 and much of this appears to have pre-industrial natural origins. 84 Based on historical production 85 of HFCs and HCFCs that are potential sources of TFA as well as projections of future uses, 77 an estimate of total production was made (Table 1).…”
Section: Fluorinated Substancesmentioning
confidence: 99%
“…Samples of rain and surface waters (oceans, rivers, lakes, and springs ) have been obtained from many geographical areas (USA, Canada, Australia, South Africa, Germany, Israel, Ireland, France, Switzerland, Finland) and show that TFA is a ubiquitous contaminant of the hydrosphere (Frank et al, 1996;Zehavi and Seiber, 1996;Grimvall et al, 1997;Wujcik et al, 1998), with values up to 40900 ng/l (Zehavi and Seiber, 1996). The average TFA concentration in rain water observed in Bayreuth during 1995 was 100 ng/l (Frank et al, 1996).…”
Section: Atmospheric Production and Fate Of Trifluoroacetic Acidmentioning
confidence: 99%